Bioscopic Books - Guns, Tine; Kunsthal Gent; Ketelers, Inge; Vanhee, Isolde (Gent : Grafische Cel, LUCA School of Arts, 2021)
Snow, Michael ; Soto Climent, Martin ; Kruithof, Anouk ; Duval, Céline ; Cramer, Daniel Gustav ; Guns, Tine ; Schmidt, Michael ; Vanoverberghe, Sybren ; Douglas, Helen ; Stokes, Telfer ; Long, Richard ; Fulton, Hamish ; Lempert, Jochen ; Kitagawa, Koji ; Feldman, Hans-Peter ; Tillmans, Wolfgang ; Laita, Alessandro ; Rizzi, Chiaralice ; Aëgerter, Laurence ; Carlier, Sarah ; Duval, Céline ; Vignale, Angelo ; Richter, Hans ; Gräff, Werner ; Balz, Lewis ; Burgin, Victor ; Clavarino, Federico ; Araki, Nobuyoshi ; Goiris, Geert ; Pinckers, Max ; Weiner, Lawrence ; Rezza, Massimiliano Tommaso ; Fowler, Luke ; Graham, Paul ; Fukase, Masahisa ; Martens, Els ; Konrad, Aglaia ; Casanova, Tiago ; van Beek, Ruth ; Graziani, Stefano ; Kuwajima, Ikuru ; Boivin, Thomas ; Bismuth, Pierre ; Plissart, Marie-Francoise ; Van der Elsken, Ed ; Mestdagh, Roberte ; de Mey, Annelies ; Doyle, Eamon ; Kooiker, Paul ; Schmidt, Michael ; Richter, Gerhard ; Prince, Richard ; Abidi, Bani ; Waart, Robin ; Broomberg, Adam ; Chanarin, Oliver ; Stig, Martine ; Palyga, Tatyana
Bioscopic Books, Kunsthal Gent, April 24th till June 12th, 2021
boek